Erosion and Surface Runoff on Forest and Oil Palm Plantation in Jalemu Watershed, Gunung Mas Regency, Central Kalimantan Province - Jaya, Adi; Birawa, Cakra; Adji, Fengky Florante; Anwar, Mochamad; Banuwa, Irwan Sukri (JOURNAL OF TROPICAL SOILS, 2018)
Changes of land cover from forest to non-forest areas affect the hydrological cycle and water quality in watershed ecosystems, such as the change of forest into oil palm plantation areas. Increased production and extention of oil palm plantations have impacts on the environment and water quality, which have become one of the environmental issues. The study was conducted to provide an overview of the erosion and surface runoff from forest and oil palm plantations and their impacts on the water quality. Erosion plots with the size of 15 m Ã— 25 m were made on Jalemu Watershed, Gunung Mas Regency, Central Kalimantan Province. The research was conducted to study the impact of land cover changes on erosion and surface runoff and nutrient loss into the Jalemu River Basin. Sampling of sediments and runoff water was carried out from the erosion plots, inlcuding water sampling from Jalemu watershed. The results showed that the erosion and surface runoff that occurred in the 5 years old oil palm area were higher than in the forest area, which implied the loss of nutrients from oil palm plantation areas and the potential for water pollution by the nutrients.